The Effect of Reductions in Concentration on Income Distribution - Powell, Irene (The Review of Economics and Statistics, 1987)
The simulation model of this study indicates that a decline in above n ormal profits associated with concentration will cause a redistribution of incom e from the highest of six income classes to low and middle income classes. The m agnitude of gains and losses range from 0.2 to 0.9 percent of income for reducti ons in four-firm concentration ratios to 50 percent in all manufacturing industr ies. The methodology uses consumer expenditure data and input-output information to estimate the impact on payments made to capital, and uses income tax data on income sources by income class to estimate the impact on income received from c apital ownership. Estimates of the change in profits resulting from a change in concentration are based on a published concentration-profits regression. Copyright 1987 by MIT Press.